2017
DOI: 10.1177/0959651817733222
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle lateral control in the presence of uncertainty for lane change maneuver using adaptive sliding mode control with fuzzy boundary layer

Abstract: Recent researches on advanced driver-assistance systems indicate great advances in terms of safety and comfort in automated driving. Advanced driver-assistance systems use control systems to perform most of the maneuvers as performed by the driver in the past. One of the useful advanced driver-assistance systems is automatic lane change system in order to avoid accidents. This study designs the controller of an automatic lane change system for an autonomous vehicle. The control law in this study is adaptive sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 62 publications
0
55
0
Order By: Relevance
“…Do not brake A sliding mode control algorithm is designed because of its robustness [35], usually designed in two steps. The first step is to design a sliding surface, and the second step is to design a control law, which drives or keeps the states to the designed sliding manifold [36].…”
Section: Elsementioning
confidence: 99%
“…Do not brake A sliding mode control algorithm is designed because of its robustness [35], usually designed in two steps. The first step is to design a sliding surface, and the second step is to design a control law, which drives or keeps the states to the designed sliding manifold [36].…”
Section: Elsementioning
confidence: 99%
“…Considering factors such as stability, comfort and optimal fuel consumption, each path has advantages and disadvantages. Norouzi et al have investigated some functions for the most optimum path . Their results indicated that using a fifth order linear function leads to the best performance.…”
Section: Controlmentioning
confidence: 99%
“…The notations y and y la are used to refer to the real values for the lateral and look-ahead lateral position. Finally, these equations can be summed up into equation (6).…”
Section: Vehicle and Driver Modelling Adaptive Fuzzy Vehicle Modelmentioning
confidence: 99%
“…where As seen in equations (6) and 7, variable k ð Þ consist of the past variables (lateral positions) and functions of past variables (). However, consist only of the consequent parameters.…”
Section: Vehicle and Driver Modelling Adaptive Fuzzy Vehicle Modelmentioning
confidence: 99%